Light Harvesting and Photoemission by Nanoparticles for Photodynamic Therapy. (19th December 2013) - Arguinzoniz, Amaia Garaikoetxea; Ruggiero, Emmanuel; Habtemariam, Abraha; Hernández‐Gil, Javier; Salassa, Luca; Mareque‐Rivas, Juan C.
<x xml:space="preserve">Abstract</x> This review provides an overview of recent efforts to utilize light harvesting and photoemission by nanoparticles (NPs) for photodynamic therapy (PDT) applications. In particular, it focuses on the recent use of quantum dots (QDs) and upconverting nanophosphors (UCNPs), which over the past decade have captivated considerable interest in biomedical research as new classes of fluorescent probes for in vivo biomolecular and cellular imaging. Increasingly, the unique properties of QDs and UCNPs are becoming the focus of attention in PDT as an emerging cancer treatment modality where a photosensitizer molecule (PS) exposed to light of a wavelength matching its absorption spectrum mediates cytotoxic effects. An overview of the processes and approaches that have been used to induce and optimize photoinduced energy and charge transfer processes and generation of different cytotoxic species ranging from reactive oxygen species to inorganic metal‐based drugs using these NPs, as well as for their targeted delivery in a cell‐ or tissue‐specific manner is presented. The main challenge for nanomaterials entering mainstream clinical practice is understanding and overcoming their toxicity. Hence, some of the known mechanisms by which QDs and UCNPs can cause unwanted toxicity are briefly reviewed, as well as how they can be minimized.